The diagnostic performance of ultrasound-guided core biopsy in the diagnosis of head and neck lymphoma: results in 226 patients. Issue 4 (April 2021) - Cuenca-Jimenez, T.; Chia, Z.; Desai, A.; Moody, A.; Ramesar, K.; Grace, R.; Howlett, D.C.
Abstract: Many clinical guidelines for investigating lymphomas advise that surgical excision biopsy (SEB) should be performed for a confident diagnosis. It is increasingly recognized in clinical practice that ultrasound-guided core needle biopsy (USCNB) is a reliable diagnostic technique. We aimed to investigate the diagnostic efficacy of USCNB in head and neck lymphoma. A retrospective analysis of all diagnosed head and neck lymphomas between 2013 and 2018 was performed. Patient records, radiology and histopathology reports along with the biopsy technique: fine needle aspiration cytology (FNAC), USCNB, and SEB used were reviewed. The technique providing diagnosis and leading to initiation of treatment was identified. Two-hundred and thirty patients and 267 biopsy samples were included. A total of 226 patients underwent USCN. In 215 of 226 (95.1%) USCNB patients were fully diagnostic allowing for initiation of oncological treatment; 11 patients required a subsequent SEB to provide diagnosis. In four patients, SEB was the only investigation performed. Of the USCNB total number of procedures (number of patients n  = 230 is the same coincidentally as the number of USCNB procedures), 215 of 230 (93.5%) were fully diagnostic samples. In the majority of cases, USCNB provided a definitive diagnosis allowing initiation of oncological treatment, avoiding the need for SEB. USCNB should be considered the first-line diagnostic modality in appropriate cases, as it reduces time to initiate treatment, costs and avoids patients having to undergo unnecessary surgery and possible complications.